Information verification and encryption based on phase retrieval with sparsity constraints and optical inference. (January 2017) - Zhong, Shenlu; Li, Mengjiao; Tang, Xiajie; He, Weiqing; Wang, Xiaogang
Abstract: A novel optical information verification and encryption method is proposed based on inference principle and phase retrieval with sparsity constraints. In this method, a target image is encrypted into two phase-only masks (POMs), which comprise sparse phase data used for verification. Both of the two POMs need to be authenticated before being applied for decrypting. The target image can be optically reconstructed when the two authenticated POMs are Fourier transformed and convolved by the correct decryption key, which is also generated in encryption process. No holographic scheme is involved in the proposed optical verification and encryption system and there is also no problem of information disclosure in the two authenticable POMs. Numerical simulation results demonstrate the validity and good performance of this new proposed method. Highlights: An optical security system is proposed based on inference principle and phase retrieval with sparsity constraints. The primary image can only be reconstructed after the two POMs are authenticated, which improves the security levels. It allows users to authenticate the two POMs without visual observation of those images used as references. No holographic scheme is involved in the proposed optical verification and encryption system.